2003
DOI: 10.1021/jf0342021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Sulfate Concentration in Soymilk on the Microstructure of Firm Tofu and the Protein Constitutions in Tofu Whey

Abstract: The effects of calcium sulfate concentration in soymilk on the microstructure of tofu and the constitutions of protein in tofu whey were investigated. The firm tofu made with 0.4% CaSO(4).2H(2)O was found to be most uniform and continuous in the microstructure. This tofu gave the maximal tofu yield, maximal solid and protein recoveries, and the best water retention ability. The results of gel electrophoresis and the ratio of amino nitrogen to total organic nitrogen indicated that the low molecular weight prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
1
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(97 citation statements)
references
References 23 publications
7
77
1
12
Order By: Relevance
“…Determination of the water holding capacity of tofu The water holding capacity (WHC) of tofu was determined by a modification of the water retaining amount (WRA) method of Kao et al (2003). A tofu disk (20 mm diameter and 13 mm height) weighing Wb was placed on three sheets of filter paper (No.2; Advantec MFS, Inc., Tokyo, Japan) in a plastic vessel, stored for 1 h after the vessel was covered, and the sample weight was then recorded (Wa).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Determination of the water holding capacity of tofu The water holding capacity (WHC) of tofu was determined by a modification of the water retaining amount (WRA) method of Kao et al (2003). A tofu disk (20 mm diameter and 13 mm height) weighing Wb was placed on three sheets of filter paper (No.2; Advantec MFS, Inc., Tokyo, Japan) in a plastic vessel, stored for 1 h after the vessel was covered, and the sample weight was then recorded (Wa).…”
Section: Methodsmentioning
confidence: 99%
“…Although coagulant concentration has a strong relationship with protein composition, its relationship with the optimal structure of tofu has not been elucidated. However, scanning electron microscopy (SEM) studies have found that tofu retaining the most soybean proteins and water has more homogeneous and finer microstructure (Kao et al, 2003;Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resultados de pesquisa quanto às alterações na microestrutura de tofu estão relacionadas com o tipo de coagulante (PRABHAKARAN; PERERA; VALIYAVEETTIL, 2006), às condições de coagulação e à concentração utilizada do coagulante (KAO; SU; LEE, 2003).…”
Section: Análise Do Perfil De Textura (Tpa)unclassified